2018
DOI: 10.1111/jdi.12816
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pancreatic volume in acute‐onset, slowly‐progressive and fulminant type 1 diabetes in a Japanese population

Abstract: Aims/IntroductionA decrease in the size of the pancreas is observed in islet autoantibody‐positive non‐diabetic donors and acute‐onset type 1 diabetes irrespective of the diabetes duration. Little is known, however, about the relationship between the size of the pancreas and type 1 diabetes subtypes, including fulminant type 1 diabetes.Materials and MethodsWe examined the pancreatic volume (PV) in 44 adult patients with type 1 diabetes (16 acute‐onset type 1 diabetes, 18 slowly progressive type 1 diabetes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…This observation suggests that the atrophy of the pancreas is likely to begin before the onset of T1D. Very recently, we also reported that the pancreatic volume assessed by CT was significantly reduced in the newly diagnosed acute-onset T1D patients, but not in the virus-induced fulminant T1D patients, when compared to non-diabetic controls (non-DCs) [15]. These findings suggest that the autoimmune process contributes to the pathogenesis of reduced PV in acute-onset T1D.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…This observation suggests that the atrophy of the pancreas is likely to begin before the onset of T1D. Very recently, we also reported that the pancreatic volume assessed by CT was significantly reduced in the newly diagnosed acute-onset T1D patients, but not in the virus-induced fulminant T1D patients, when compared to non-diabetic controls (non-DCs) [15]. These findings suggest that the autoimmune process contributes to the pathogenesis of reduced PV in acute-onset T1D.…”
Section: Introductionsupporting
confidence: 52%
“…Iodine contrast medium ( Iomeron 300, Eisai, Tokyo, Japan; Omnipaque 300, Daiichi-Sankyo, Tokyo, Japan; Iopamiron 300, Bayer Health Care, Leverkusen, Germany) was intravenously injected at a rate of 3.0 mL/s by a power injector. The pancreas was manually outlined on axial image slices for semi-automatic calculation of the pancreatic volume using Ziostation2 (Ziosoft Inc., Tokyo, Japan) software according to the methods previously reported [15]. The areas of the slices were summed throughout the volume of the pancreas.…”
Section: Measurement Of Pancreatic Volumementioning
confidence: 99%
“…Sasamori et al recently revealed that unlike that in the participants with acute-onset type 1 diabetes and SPIDDM, pancreatic volume (PV) was not decreased in the participants (mainly) with classic fulminant type 1 diabetes, irrespective of disease duration, as compared with that in the control participants [16]. These findings suggest the possibility of no pre-existence of pancreatic inflammation until just before the onset of fulminant type 1 diabetes.…”
Section: Discussionmentioning
confidence: 95%
“…Potential explanations for the reduction in pancreas size in type 1 diabetes include loss of insulinotrophic effects on acinar cells and immunologic destruction of exocrine pancreatic tissue (16). Interestingly, pancreatic size is also reduced in fulminant type 1 diabetes, type 2 diabetes, and monogenic diabetes, implicating potentially overlapping mechanisms related to b-cell dysfunction (17)(18)(19). Other factors that may impact pancreas size are likely complex interactions between genetics, epigenetics, and environmental agents (20).…”
mentioning
confidence: 99%